Thermolabile Methylenetetrahydrofolate Reductase and Factor V Leiden in the Risk of Deep-Vein Thrombosis - Kluijtmans, Leo A. J.; Heijer, Martin den; Reitsma, Pieter H.; Heil, Sandra G.; Blom, Henk J.; Rosendaal, Frits R. (Thrombosis and Haemostasis, 1998)
Mild hyperhomocysteinemia is an established risk factor for both arteriosclerosis and thrombosis, and may be caused by genetic and environmental factors. Methylenetetrahydrofolate reductase (MTHFR) catalyzes the reduction of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate, the cofactor for the methylation of homocysteine to methionine. Individuals with the thermolabile variant of MTHFR have decreased MTHFR activities, resulting in elevated plasma homocysteine concentrations. A homozygous 677C→T transition in the MTHFR gene has recently been identified as the cause of reduced enzyme activity and thermolability of the protein. We studied the frequency of the homozygous mutant (+/+) genotype in 471 patients with deep-vein thrombosis and 474 healthy controls enrolled in The Leiden Thrombophilia Study (LETS), its interaction with factor V Leiden, and assessed the association between the MTHFR genotypes and plasma homocysteine concentration. Homozygosity for the 677C→T polymorphism was observed in 47 (10%) patients, and in 47 (9.9%) controls (OR 1.01 [95% CI: 0.7-1.5]). No modified risk of the (+/+) genotype was observed in carriers of factor V Leiden. Our data suggest that, although the homozygous mutant genotype is associated with elevated plasma homocysteine concentrations, this homozygous mutation itself is not a genetic risk factor for deep-vein thrombosis, irrespective of factor V Leiden genotype.